PERSONHOOD AND EPISTEMIC INTERACTIVISM IN INDIGENOUS ESAN THOUGHT (2016)
Epistemic interactivism, an aspect of the epistemology of representation, is a cognitive intercourse between the subject and person-object of knowledge that underlies the conception of a person in Esan thought. Earlier studies separated the subject from the object of knowledge, and classified persons and non-persons as object of knowledge. This separation ignored the cognitive and moral values of persons, thereby creating a dehumanised relationship between the subject and person-object of knowledge. This study, therefore, employed epistemic interactivism in re-constructing the relationship between the subject and person-object of knowledge. This is with a view to re-establishing the cognitive and moral values that distinguish persons from non-persons upon which personhood is grounded in Esan thought. This study adopted Hegel’s dialectics which unified the subject and object of knowledge at the “Absolute”. Major works on epistemology, specifically Hegel’s The Phenomenology of Mind (TPM), Descartes’ A Discourse on Method (ADM), Locke’s An Essay Concerning Human Understanding (ECHU), and works on Esan culture, particularly Okojie’s Words of Wisdom from Ishan Elders (WWIE), and Esan Native Laws and Customs (ENLC), were purposively selected. These works articulated the traditional theories of representation, personhood and epistemic interactivism. The conceptual method was used to clarify concepts such as representation, personhood and epistemic interactivism. Critical analysis was employed to explain the dehumanising problems in the traditional theories of representation, and the re-constructive method was used to re-establish the cognitive and moral values of a person in epistemic interactivism. Traditional theories of representation separated subject and person-object of knowledge, grouping person-object and non-person-object (ADM, ECHU). This separation ignored the cognitive and moral values of persons, creating propositional knowledge that dehumanised the relationship between the subject and person-object of knowledge (ADM), and the possible unity of the subject and object of knowledge at the “Absolute” (TPM). However, Esan culture distinguishes persons from non-persons, bonding the subject and person-object of knowledge to arrive at an epistemic intercourse as captured by the Esan dictum: ai yole abha len oria (we never say we do not know someone) (ENLC, WWIE). Critical interrogation revealed that conventional theories of representation were influenced by the materialism of Western science that described persons and non-persons impersonally, ignoring the human values of cognition and morality. These cognitive and moral values formed the basis of personhood in Esan thought, such that the subject engages in an epistemic intercourse with the person-object of knowledge in a way that sustains the dignity of persons, creating the grounds for a humane relationship between the subject and person-object of knowledge. Conventional theories of representation separated the subject and person-object of knowledge, ignoring the cognitive and moral values of persons and creating a dehumanised relationship between the subject and person-object of knowledge. Epistemic interactivism of Esan thought, which unified the subject and person-object of knowledge on cognitive and moral grounds, provides adequate basis for person-hood and resolving the dehumanised relationship between the subject and person-object of knowledge